The Role of R&D Expenditure on Job Creation in the Malaysian Manufacturing Sector - Sabri Nayan; Siti Nur Fatihah Samsuddin; Aznita Samsi; Norehan Abdullah; Selamah Maamor; Hussin Abdullah (International Journal of Supply Chain Management, 2019)
In order to remain competitive in the world economy, Malaysia needs to constantly generate and establishes new sources for economic growth and job creation. One of the means of achieving such a goal is to increase the nation capability and effectiveness in adopting, developing and translating science and technology through Research and Development (R&D). However, until now still unclear interpretation between employment and job creation. Resulting in the unsettled issue of the relationship between R&D and job creation. Thus, the present paper attempts to examine and establish the relationship between R&D and job creation by using GMM-System across 54 industries in the Malaysian manufacturing sector. The empirical evidence provided in this paper suggests that R&D significantly determined job creation. R&D policy can contribute a positive effect on job creation in the Malaysian manufacturing sector. This is indeed in line with the National Science, Technology and Innovation Policy that aims to expand Malaysia’s gross expenditure on R&D by at least 2 percent prior to the year 2020.